SARS-CoV-2 transmission across age groups in France and implications for control - Cécile Tran Kiem (Nature Portfolio, 2021)
In this study, Tran Kiem et al. examine the contribution of different age groups to COVID-19 transmission. Using data from the French epidemic in summer 2020, they report that while individuals aged 80 years and older are more at risk, pandemic control in the absence of vaccines required measures targeted at all age groups.